(untitled) (Papeles, 2021)
In this article we analyze the participatory public policies in the framework of a reflection on the conditionings of the scale in the public representation of the public as the common. We understand scale as the way a territory is organized. This can be presented in a decentralized way and therefore refer to the neighborhood as its primary or centralized unit and reach the city as a whole. From the point of view introduced here, the territories are configured as scenarios that enable citizens to produce different representations about the public. The analytical path made in this research allows us to maintain that the major scales positively affect the public representation of the public as the common. Conversely, as the scale diminishes the common carácter of the public becomes fragmented.